The impact of rapid weight loss on the leptin, adiponectin levels, and insulinresistance among adult free style wrestlers - Mohammad, T.; Farzad, N.; Mohammad Tagie, G.; Ranjbar, K. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Recent studies, shows the effective role of adipose tissue as an active endocrine organ. Leptin level increases in obese bodies while adiponectin as an antirisk factor reduction that contributes to decrease insulin resistance and anthropometric profiles. Hence, expected to the negative effects of weight loss on wrestlers' physiological function; leptin and adiponectin behaviors and insulin resistance in young wrestlers during their rapid weight loss program were examined.